Translocation of Clostridium difficile Toxin B across Polarized Caco-2 Cell Monolayers Is Enhanced by Toxin A - Tim Du; Michelle J Alfa (Canadian Journal of Infectious Diseases)
Clostridium difficile is the etiological agent of antibiotic-associated diarrhea; the most common form of nosocomial infectious diarrhea. The basis for the shock-like systemic symptoms observed in severe cases of this infection are not known. It is hypothesized that the invasion of C difficile toxins A and/or B from the gut mucosa may contribute to these symptoms.